Correction to: Molecular mechanics and dynamic simulations of well-known Kabuki syndrome-associated KDM6A variants reveal putative mechanisms of dysfunction - Chi, Young-In; Stodola, Timothy J.; De Assuncao, Thiago M.; Leverence, Elise N.; Tripathi, Swarnendu; Dsouza, Nikita R.; Mathison, Angela J.; Basel, Donald G.; Volkman, Brian F.; Smith, Brian C.; Lomberk, Gwen; Zimmermann, Michael T.; et al. (Orphanet journal of rare diseases, 2021)
An amendment to this paper has been published and can be accessed via the original article.